2020
DOI: 10.1038/s41598-020-74066-0
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic microenvironmental preconditioning enhance neuroprotective properties of human mesenchymal stem cells derived from Wharton's Jelly (WJ-MSCs)

Abstract: Tuning stem cells microenvironment in vitro may influence their regenerative properties. In this study Wharton's Jelly-derived mesenchymal stem cells (WJ-MSCs) were encapsulated in 3D hydrogels derived from human fibrin (FB) or platelet lysate (PL) and the oxygen level was adjusted to physiological normoxia (5% O2). The influence of the type of the scaffold and physiological normoxia conditions was tested on the WJ-MSCs' survivability, proliferation, migratory potential, the level of expression of selected tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…The spontaneous differentiation of hWJ-MSCs towards neural lineages observed in the current study confirmed our previous findings [ 18 , 22 , 64 , 66 , 81 ]. Drela et al [ 18 ] described enhanced neuronal and glial differentiation of hWJ-MSCs as compared to hBM-MSCs cultured under 21% O 2 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The spontaneous differentiation of hWJ-MSCs towards neural lineages observed in the current study confirmed our previous findings [ 18 , 22 , 64 , 66 , 81 ]. Drela et al [ 18 ] described enhanced neuronal and glial differentiation of hWJ-MSCs as compared to hBM-MSCs cultured under 21% O 2 .…”
Section: Discussionsupporting
confidence: 92%
“…Despite the lack of cell–cell contact, hWJ-MSCs significantly reduced apoptosis of neurons in the hippocampal CA1 region via secretion of neuroprotective factors in both tested oxygen conditions (21% O 2 and 5% O 2 ). A similar neuroprotective effect independent of the oxygen concentration was also observed by Lech et al [ 81 ] for hWJ-MSCs cultured in 3D hydrogel scaffolds. Puig-Pijuan et al also proved potential neuroprotective and antioxidants effects of WJ-MSCs on hippocampal cultures [ 86 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Studies have con rmed that CD-ECM could guide intricate cellular and tissue processes such as homeostasis, healing and regeneration [8]. Wharton's Jelly-derived mesenchymal stem cells (WJ-MSCs) is acquired from umbilical cord tissue with the ability to large amount of endogenous ECMs [9][10][11]. The ECM derived from WJ-MSCs contains abundant collagenic structural proteins, and other ECM components such as bronectin and laminin [12].…”
Section: Introductionmentioning
confidence: 99%